The advantages of artificial intelligence-based gait assessment in detecting, predicting, and managing Parkinson’s disease - Wu, Peng; Cao, Biwei; Liang, Zhendong; Wu, Miao (Frontiers in Aging Neuroscience, 2023)
Dear editor, I wish to submit a manuscript entitled “Positive Roles of Gait Evaluation Based on Artificial Intelligence in Parkinson's Disease: Detection, Prediction, and Management” to be considered for publication as a review in Frontiers in Neurology. The paper was coauthored by PW, DL and WM. Recent studies have evaluated gait patterns from PD patients using techniques based on artificial intelligence (AI). These novel methods have improved diagnostic efficiency, prevented freezes, and increased motor independence of PD patients. This article provides a detailed review of the widespread use and effectiveness of AI-based gait evaluation systems in PD. Further, the current state and limitations of the art are assessed to provide guidance for further studies. We believe that our study makes a significant contribution to the literature because early detection of PD and automatic prediction of freeze episodes are especially crucial for long-term symptom monitoring and preemptive mitigation. AI-based gait evaluation systems are promising to be a potential tool for clinical decision-making and treatment support. We anticipate that this paper will be of interest to the readership of your journal because to the best of our knowledge there is no published reviews on introduction and highlighting the positive roles of AI-based gait evaluation in PD. This manuscript has not been published or presented elsewhere in part or in entirety and is not under consideration by another journal. All study participants provided informed consent, and the study design was approved by the appropriate ethics review board. We have read and understood your journal’s policies, and we believe that neither the manuscript nor the study violates any of these. There are no conflicts of interest to declare. Thank you for your consideration. I look forward to hearing from you. Sincerely,